Setting the ball rolling on post-transplant cardiac rehabilitation in India - Priya Chockalingam; Vaishnav Natarajan; Tharani Sekar; K.G. Sureshrao; K.R. Balakrishnan (IHJ Cardiovascular Case Reports, 2022)
Post-transplant cardiac rehabilitation reduces major adverse cardiac events and improves long-term survival but is nonexistent in India. This case series shows that cardiac rehabilitation improves health-related behaviour, health-related quality of life and functional capacity in heart transplant recipients and could potentially be considered in the routine management of this growing population in India.